Reliability and sensitivity to change of post-match physical performance measures in elite youth soccer players - Franceschi, A.; Robinson, M. A.; Owens, D.; Brownlee, T.; Bravo, D. F.; Enright, K. (Frontiers in Sports and Active Living, 2023)
Introduction: To effectively monitor post-match changes in physical performance, valid, reliable and practical measures which are sensitive to change are required. This study aimed to quantify test-retest reliability and sensitivity to change of a range of physical performance measures recorded during an isometric posterior chain (IPC) lower-limb muscle test and a countermovement jump (CMJ) test.